2021
DOI: 10.3390/ijerph18189461
|View full text |Cite
|
Sign up to set email alerts
|

Experience of a Neuro-Emergency Expert in the Emergency Department during One Year of the COVID-19 Pandemic

Abstract: We aimed to evaluate the overall clinical characteristics of patients treated by a neuro-emergency expert dedicated to the emergency department (ED) as an attending neurologist during the COVID-19 pandemic. We included adult patients who visited the ED between 1 January and 31 December 2020 and were treated by a neuro-emergency expert. We retrospectively obtained and analyzed the data on patients’ clinical characteristics and outcome. The neuro-emergency expert treated 1155 patients (mean age, 62.9 years). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…A Korean study, found that dizziness, followed by motor weakness and altered mental status were the top 3 complaints in 2020. 4 Our study also found a significant change on neurologic chief complaints at the ER. Patients complaining of motor weakness increased from 14.1% to 19% in 2020.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A Korean study, found that dizziness, followed by motor weakness and altered mental status were the top 3 complaints in 2020. 4 Our study also found a significant change on neurologic chief complaints at the ER. Patients complaining of motor weakness increased from 14.1% to 19% in 2020.…”
Section: Discussionsupporting
confidence: 67%
“…They were also able to conclude that stroke was particularly more common among patients who are 40 year-old and above and metabolic encephalopathy was found among 60 year-old and older patients. 4 In this study, newonset stroke remained more common among male than female before and during the pandemic with almost similar proportions. Interestingly, new onset encephalopathy was more common among female patients before the pandemic but was found more common among male during the pandemic.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This 900-bed facility has a regional emergency medical center, as designated by the government, and receives approximately 75,000 ED visits annually. In our neuro-emergency medicine project [ 14 ], a neuro-emergency expert was responsible for the emergency care of patients with neurological symptoms. Through a systematic review of electronic medical records between 1 January 2020 and 31 December 2021, patients aged ≥18 years with neurologic symptoms treated by a neuro-emergency expert in the ED were screened.…”
Section: Methodsmentioning
confidence: 99%